The bullet that missed - Osman, Richard, 1970- (Osman, Richard, 1970- Thursday Murder Club mystery., 2022)
It is an ordinary Thursday, and things should finally be returning to normal. Except trouble is never far away where the Thursday Murder Club are concerned. A decade-old cold case--their favorite kind--leads them to a local news legend and a murder with no body and no answers. Then a new foe pays Elizabeth a visit. Her mission? Kill or be killed. Suddenly the cold case has become red hot. While Elizabeth wrestles with her conscience (and a gun), Joyce, Ron, and Ibrahim chase down the clues with help from old friends and new. But can the gang solve the mystery and save Elizabeth before the murderer strikes again?